Examining the structural design of deep pile foundation bridge under different directions of water movement - Hakim, Ahmed Saeed (Edelweiss Applied Science and Technology, 2025)
The impact of water movement presented by currents and waves poses significant challenges to marine structures, particularly in the structural design of bridge structures. Pile foundation bridges, extending into the sea, are particularly susceptible to variations in the direction of these forces. This study investigates the structural response of such structures to directional changes in current-wave forces. A series of numerical simulations were performed using ABAQUS software to model the interaction of current and wave forces with varying directions. The study examined the dynamic response of bridge piers, specifically in terms of acceleration and displacement under multiple load conditions along the pile cap foundation. To validate the numerical results, previous experimental studies were considered. The findings show that the inherent frequencies of the bridge pier are increased when water is present. The greatest dynamic response was observed when the current-wave forces were longitudinal (90°), compared to other directional combinations (0°, 45°, 135°, and 180°). The influence of the directional disparity between current and wave forces is substantial and must not be overlooked in bridge design. Therefore, accounting for the interaction between current and wave direction is critical for the structural integrity of deep-water bridges.